Subjective processes surgical treatment in patients with stages of the disease hemorrhoidal - Freitas,Magno Otávio Salgado de (2017)
Abstract Introduction Hemorrhoidal disease afflicts 4.4% of the world population, being the most common anal disorder. Surgical treatment is used for about 5-10% of cases where conservative procedures have not worked. Objective To understand the trajectory and perception of individuals submitted to surgical treatment of hemorrhoidal disease. Methods This is a descriptive study with a qualitative approach, which emphasized Cartography as the main method in the analysis of the results. Data were produced through individual interviews recorded and transcribed in full, from March to June 2015, in a Polyclinic and in a public hospital in the municipality of Montes Claros-MG. Twelve interviews were carried out. Results The results evidenced the existence of processes of subjectivization that, through affectations, cause individuals to demonstrate a transcendent thought, exemplified by the sensation of a self-knowledge of the disease, including correlating it with possible hereditary, behavioral and alimentary causes. There was an escalation in the various levels of health care, standardized by the public system, sometimes revealing a molar thought, preventing the occurrence of an event, reducing power and failing to achieve a plan of immanence with the complete resolution of the problem. The hard lines, evidenced by a delay in obtaining a treatment thanks for fear and shame, favored self-medication, with a worsening of symptoms. Conclusion It was noted that there were obstacles in all levels of the SUS that made it difficult to reach the surgical treatment, but all patients were considered with surgery and with the postoperative period.